Former à et par la collaboration numérique : quels enjeux pour l’enseignement universitaire ? - Catherine DE LAVERGNE; Marie-Caroline HEÏD (Tic & Société)
The conception of hybrid courses, linking class sessions and online activities, aims to encourage the emergence of different ways of learning, exploiting opportunities offered by various digital collaboration technologies. However when courses are directed at students who expect to become future professionals in the fields of information and communication, digital collaboration is not only a means but also a goal, in order to favor the emergence of professional competencies that are required for their integration in a professional environment. The purpose of this article is to identify issues involved in the conception and implementation of a training system using digital collaboration. Different layouts, revealing tensions, will be illustrated from experiments realized in France, at the University of Montpellier.